Pengembangan Taman Baca Masyarakat di Al-Azhari, Kec. Medan Labuhan Kota Medan - Asmita Khoiriyah Manurung; Nur Santri; Reni Ayu Pratiwi; Anggriani Anggriani; Yusniah Yusniah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The library is one of the many facilities that has many benefits and is most favored by parents for the knowledge needs of their children or commonly known as a bridge of knowledge. The community-made reading garden is a place that is built and cared for by both the community and the local government, which is useful as a learning facility as well as the knowledge of local residents in improving the quality of the local community's children. The purpose of building this reading garden is to increase community interest, as a place for learning activities for young children and adults, as well as create and create the independence of citizens with skilled activities that can later benefit the community. This research was conducted to determine the role of the al-Azhari reading center which is very helpful to the community, especially kindergarten children and elementary school level students.